2006
DOI: 10.1038/sj.ejcn.1602370
|View full text |Cite
|
Sign up to set email alerts
|

Dietary and genetic determinants of homocysteine levels among Mexican women of reproductive age

Abstract: Objective: To evaluate the independent and joint effects of dietary folate, vitamin B 12 consumption and methylenetetrahydrofolate reductase (MTHFR) polymorphisms (677C4T and 1298A4C) on the circulating folate and homocysteine (Hcy) levels among Mexican women of reproductive age. Design: A cross-sectional, population-based study. Subjects: The first 130 healthy non-pregnant women (aged 16-34 years) who agreed to participate in a reproductive cohort in Morelos, Mexico. Main outcome measurements: Dietary intakes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 37 publications
1
21
0
Order By: Relevance
“…According to estimates by the National Nutrition Survey, in Mexico, 34.7 % of women aged 12-49 years have an inadequate consumption of folate (Barquera et al 2003). Although there is no information about the deficiency of vitamin B 12 intake at the population level, in previous reports with non-pregnant women of reproductive age in the same population, we found a dietary vitamin B 12 deficiency of 15.4 % (Torres- Sánchez et al 2006) and 21.3 % of pregnant women during the first trimester of pregnancy (Del Río-García et al 2009). …”
Section: Introductionmentioning
confidence: 57%
See 1 more Smart Citation
“…According to estimates by the National Nutrition Survey, in Mexico, 34.7 % of women aged 12-49 years have an inadequate consumption of folate (Barquera et al 2003). Although there is no information about the deficiency of vitamin B 12 intake at the population level, in previous reports with non-pregnant women of reproductive age in the same population, we found a dietary vitamin B 12 deficiency of 15.4 % (Torres- Sánchez et al 2006) and 21.3 % of pregnant women during the first trimester of pregnancy (Del Río-García et al 2009). …”
Section: Introductionmentioning
confidence: 57%
“…Dietary sources of vitamin B 12 included: liver, sardines, tuna, pork, lamb, beef, dairy, eggs, fish, chocolate, beer and white and red wines. This methodology is described in two previous studies where we used this program (Torres-Sánchez et al 2006;Del Río-García et al 2009). …”
Section: Prenatal Evaluationmentioning
confidence: 99%
“…The frequency of consumption of 95 items with predetermined portions was classified according to 10 response categories, going from ‘never’ up to ‘six times per day’. Nutrient intake including folate, vitamin B 12 , calcium, iron and zinc was estimated through a computer program developed by the University of Texas (Food Intake Analysis System [FIAS] 3.0) and used previously in other similar populations (Torres et al, 2006; López-Carrillo et al, 1999). More details on the methodology are available elsewhere (Río García et al, 2009).…”
Section: Methodsmentioning
confidence: 99%
“…Of the remaining 38 studies, 7 studies reported using MAs, 28 reported using PBAs (e.g., chemiluminescent immunoassay), 1 reported use of both a PBA and LC-MS/MS to measure plasma folate and RBC folate, respectively (50), and 2 did not report assay method used (48,51). The 2 unknown assay studies and 3 PBA studies that specifically used the BRQ II RIA (52)(53)(54) were restricted to tier 2 analyses. In the case of the study that used 2 methods, RBC folate values were not used in meta-analyses because it was the only study to use LC-MS/MS (50).…”
Section: Study Characteristicsmentioning
confidence: 99%